2016
DOI: 10.1002/jor.23164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sagittal plane mechanics on ACL strain during jump landing

Abstract: ABSTRACT:The relationships between non-contact anterior cruciate ligament injuries and the underlying biomechanics are still unclear, despite large quantities of academic research. The purpose of this research was to study anterior cruciate ligament strain during jump landing by investigating its correlation with sagittal plane kinetic/kinematic parameters and by creating an empirical model to estimate the maximum strain. Whole-body kinematics and ground reaction forces were measured from seven subjects perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 47 publications
4
56
2
Order By: Relevance
“…Bakker et al [9] examined the effects of sagittal plane kinematics on ACL strain in drop landings using a combined in vivo/computational/in vitro methodology. This involved inputting motion capture data into a musculoskeletal computer model of the lower extremities to estimate the forces that cross the knee.…”
Section: Introductionmentioning
confidence: 99%
“…Bakker et al [9] examined the effects of sagittal plane kinematics on ACL strain in drop landings using a combined in vivo/computational/in vitro methodology. This involved inputting motion capture data into a musculoskeletal computer model of the lower extremities to estimate the forces that cross the knee.…”
Section: Introductionmentioning
confidence: 99%
“…Women also are more likely than men to exhibit aberrant and asymmetric lower extremity movement patterns both before and after ACL injury . Aberrant and asymmetric movements may not only play a role in primary ACL injury risk, but also influence the development and progression of post‐traumatic osteoarthritis . While movement asymmetries may persist years after ACLR, little is known about the effect of post‐operative rehabilitation programs on movement patterns, particularly in women, after ACLR.…”
mentioning
confidence: 99%
“…This indicated that participants in the IFA group displayed stiffer landing strategies in the sagittal plane, which studies have associated with greater strain to the anterior cruciate ligament. 29 Researchers and clinicians have begun to study the efficacy of gait retraining as an intervention strategy to address some of the common injuries experienced by runners. Crowell and Davis 30 studied the efficacy of a gait retraining program designed to reduce lower extremity loading during running.…”
Section: External Focus Of Attentionmentioning
confidence: 99%